PHYTOCHEMICAL, ANTIMICROBIAL AND TOXICITY STUDIES OF Ocimum gratissimum LEAF (SCENT LEAF) - A, BABAGANA; FATIMAH, M. M.; HAUWA, A. B; AHMED M.; MAIYAMA, S. Y.; YAHAYA, A., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2023)
The present study investigated the phytochemical, antimicrobial and toxicity studies of Ocimum gratissimum leaf. The leaves were extracted using n-hexane, ethyl acetate and methanol. Phytochemical screening was carried out on the three extracts to check for the presence of plant metabolites. Antimicrobial activity of the methanolic leaf extract was carried out using disk diffusion method and the toxicity of the leaves extracts was carried out using Drosoplila assay. The results showed the plant leaves contains secondary metabolites such as tannins, saponins, flavonoids, alkaloids, glycosides and steroids/terpenes among others. The in vitro antimicrobial screening of the plant extracts showed that they are potential antimicrobial agents against the tested microorganisms with S. pneumonia showing highest zone of inhibition of 16 mm at concentration of 240 mg/cm3 . Toxicity using Drosophila melanogaster flies showed the plant extracts are safe for oral consumption up to concentration of 320 mg/10g diet. The presence of these secondary metabolites suggests great potentials of the plants as a source of useful phytomedicine. Keywords: Antimicrobial activity, Drosophila melanogaster, Ocimum gratissimum, Phytomedicine